USM 54th CONVOCATION: 11 24-27 OCTOBER 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 10 August 2016 His Royal Highness the Chancellor of Universiti Sains Malaysia (USM), Duli Yang Maha Mulia Tuanku Syed Sirajuddin Ibni AlMarhum Tuanku Syed Putra Jamalullail, has given his consent for USM to commence the 54th Convocation ceremony beginning Monday, 24 October 2016 until Thursday, 27 October 2016.